The regenerative supply chain: a framework for developing circular economy indicators. Issue 23 (2nd December 2019) - Howard, Mickey; Hopkinson, Peter; Miemczyk, Joe
Abstract : There are widely differing experiences and practices in the development of indicators to monitor, report and communicate progress towards the implementation of the circular economy (CE). We present a framework for developing CE indicators which link to the core goals, principles and building blocks of a CE. To do this we utilise the Ellen MacArthur Foundation butterfly model as a coherent systems overview of key material stocks and flows, and representation of relationships between inputs, outputs, recovery processes, emissions, energy and value loops in physical and financial measures which constitute the CE supply chain. Based on nine multinational organisations and four cases of leading companies engaged with CE activity, we address the types of indicators being used and make recommendations for indicators to reflect key goals and principles of CE. Our research on the development and expansion of circular practices leads to the question of what new opportunities and challenges CE raises for such companies in terms of competitive business advantage and resultant requirements for supply chain redesign and indicator development, over and above pre-existing closed-loop production.